A 'very fowle warre': Scorched earth, violence, and Thomas Howard's French and Scottish campaigns of 1522-1523. (November 2021) - Murphy, Neil
This article examines the scorched-earth campaigns Thomas Howard, earl of Surrey, launched in France and Scotland in 1522-1523. These campaigns saw exceptional levels of violence directed against civilian populations by Tudor armies. Howard destroyed tens of thousands of acres of the countryside in France and Scotland, as well as numerous towns, villages, and strongholds. He made methodical and systematic use of scorched earth to achieve the prolonged ruination of the enemy frontiers. Overall, this article shows that Howard's campaigns of 1522-1523 represented a marked escalation in the level of violence English armies directed at civilians.